Current applications and perspectives of genomic selection in Bos indicus (Nellore) cattle - Fernandes Júnior, Gerardo Alves [UNESP]; Peripolli, Elisa; Schmidt, Patrícia Iana [UNESP]; Campos, Gabriel Soares [UNESP]; Mota, Lucio Flavio Macedo; Mercadante, Maria Eugênia Zerlotti; Baldi, Fernando [UNESP]; Carvalheiro, Roberto [UNESP]; de Albuquerque, Lucia Galvão [UNESP] (My University, 2022)
Bos indicus cattle acquired very particular traits to thrive in distinct environments based on the evolutionary adaptation process they have undergone, becoming particularly relevant for tropical production systems. In this review we present and discuss the current status of the application of genomic selection (GS) for Bos indicus (Nellore) breed, also quoting GS applications in other Bos indicus and influenced Bos indicus beef breeds raised in pasture-based tropical conditions. Traditional Bos indicus beef breeding programs have achieved expressive annual genetic gains for growth performance-related traits. Lately, higher genetic gains have been achieved through GS compared to traditional pedigree-based evaluations. With genomics, Bos indicus breeding programs have intensified the use of young bulls. Moreover, GS boosted the genetic progress for traits such as those that are measured late in animal life and are non-routinely recorded due to elevated expenses (i.e., feed efficiency, carcass and meat quality, tick resistance, male puberty-related traits). Screening for young non-proven sires to be used in commercial herds and selecting genetically superior young females through a combined adoption of genomic selection and embryo transfer are other important genomic applications. Genotyping strategy (i.e., animals and markers that should be genotyped) highly impacts the cost-effectiveness of genomic selection, and alternatives currently implemented in Bos indicus are presented. The use of whole genome sequence, multi-breed models and selection accounting for gametic variance are possibilities to enhance genomic impact. With genomics, besides growth and reproduction, traits related to quality, efficiency and sustainability of production have been included as selection criteria for Bos indicus beef cattle.
Keywords: Animal breeding; Genomic prediction; Topical cattle